SPINK1 facilitates tumor progression via the EGFR/JAK/STAT3 axis in oral squamous cell carcinoma: insights from single-cell RNA sequencing - Bao, Mingyan; Tang, Zhangui (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to elucidate the functional role and molecular mechanisms of Serine Peptidase Inhibitor Kazal Type 1 (SPINK1) in oral squamous cell carcinoma (OSCC) through integrative analysis of single-cell RNA sequencing (scRNA-seq) data.Materials and methodsCellular subpopulations within OSCC were stratified using transcriptomic datasets from the GEO database. Cell-cell communication networks were reconstructed to map ligand-receptor interactions, while Gene Set Variation Analysis (GSVA) and Gene Set Enrichment Analysis (GSEA) were employed to systematically investigate SPINK1-associated signaling pathways. SPINK1 expression profiles in OSCC tissues were validated through quantitative PCR (qPCR) and immunoblotting. Gain- and loss-of-function assays utilizing Cell Counting Kit-8 (CCK-8), wound healing assays, transwell migration/invasion chambers, and murine xenograft models were implemented to assess SPINK1-mediated oncogenic phenotypes. Rescue experiments conclusively established the EGFR/JAK/STAT3 signaling axis as the mechanistic backbone of SPINK1-driven oncogenesis.ResultsSPINK1 was closely associated with T cells, malignant cells, and an array of immune modulators, including chemokines and immunoinhibitors, throughout OSCC progression. SPINK1 operates through pathways involving JAK/STAT3, P53, Notch and WNT signaling cascades. Relative to their normal tissue counterparts, SPINK1 is upregulated in OSCC, resulting in increased cell proliferation, invasion, and migration upon SPINK1 overexpression, whereas SPINK1 knockdown has opposite effects. SPINK1 knockdown led to a significant reduction in EGFR and STAT3 phosphorylation levels, whereas exogenous supplementation of EGFR effectively rescued this phenotype.ConclusionSPINK1 has been established as a novel therapeutic target in OSCC, with its dual role in tumorigenesis and immune modulation providing a molecular foundation for developing targeted therapeutic modalities and precision oncology strategies.